KORELASI KONDISI GEOLOGI DAN SUMBER PENCEMAR TERHADAP KUALITAS AIR SUMUR DI KECAMATAN VERA CRUZ, DILI, TIMOR LESTE - Emeliano Maria Gusmão de Oliveira; Radjali Amin; Sudarmadji Sudarmadji (Universitas Lambung Mangkurat, 2022)
The research was took place in Post Administrative of Vera Cruz, Dili City, Timor Leste. Vera Cruz is one of the 5 (five) post administrative that located in Dili City. The purpose of this study was to examine the quality of well water in the research area, considering that the government supply of clean water to Dili City could not fulfill the needs of the community. By understanding the quality of well water for the community daily consumption, the community might be more confident or able to treat the well water so that it was safe for consumption. Well water samples were taken randomly from 4 villages of Vera Cruz Post Administrative. Well water quality was analyzed in the laboratory with 6 (six) parameters, including Mn, Fe, and microbiology. In addition, the distance of the well to the source of pollutant and the local geological conditions were studied to find out their influences to the quality of the well water. Referring to several standards of drinking water quality from both Indonesia and Timor Leste, it was known that well water in Vera Cruz Post Administrative has not been yet suitable for direct consumption because it was affected by domestic polluting sources and local geological conditions. Therefore, the well water should be treated before consumption.